A Matemática no cotidiano dos alunos do sétimo ano do Ensino Fundamental em uma escola pública no município de Capanema/PA - SILVA, Kelly Louise Costa da (2024)
This work is a study about Mathematics in the daily life of students in the seventh year of Elementary School in a public school in the city of Capanema/PA. We seek to contribute to the teaching and learning process through the four fundamental operations and problem solving, providing the student with not only manipulate symbols and numbers, but conduct it in such a way that it is able to perform interpretation, understanding and development of logical reasoning, in order to build in the interlocutor the ability correlated to their everyday knowledge. Aiming to identify the causes that lead students to have learning difficulties in Mathematics content, a fact that prevents continuity in the teaching and learning process in Mathematics, in relation to their practices and contexts of their day-today reality, using It uses the four fundamental operations of mathematics as a valid tool that achieves good learning results in the students of this 7th grade class. This research is based on qualitative research. As a result, teachers need to be in continuous search for pedagogical practices that relate to the student's daily life, making use of coherent techniques in the process of teaching and learning mathematics content.